Comparative Analysis of Continuous versus Reciprocating Instruments in Retreatment of Flat-oval Root Canals - Matta, Mônica C; de Araújo , Roberto Paulo C; Dantas, Eugênia Livia A; D’Assunção, Fabio Luiz Cunha; Barbosa de Sousa, Frederico (Iranian Endodontic Journal, 2021)
Introduction: Flat-oval root canals of incisors can be problematic in retreatments. This study assessed the efficacy of continuous and reciprocating rotation instruments in retreatment of flat-oval root canals in lower incisors via micro-computed tomography (micro-CT). File systems studied were ProTaper universal retreatment rotary system associated with ProTaper Next (PTUR+PTN), D-RaCe associated with iRaCe (DR+iR), Reciproc (REC), and WaveOne (WO). Materials and Methods: Thirty-two mandibular incisors with flat root canal were divided into 4 groups (n=8). The groups were initially prepared with PTN, iRaCe, REC, and WO, then instrumented, filled, and subjected to micro-CT analyses. All the canals were then retreated with the PTUR+PTN, DR+iR, REC, and WO, and then subjected to new micro-CT analysis which allowed quantification of residual filling material volume and change in the diameter of the root canal apical third. Endodontic retreatment time was also quantified. Data were analyzed with One-Way ANOVA and post hoc t tests. Results: None of the systems completely removed the filling material. The groups differed in terms of remnant filling material volume (PTUR+PTN=2.9±1.1 mm3; DR+iR=3.6±3.1 mm3; REC=4.9±1.9 mm3; WO=3.1±1.9 mm3) and retreatment time (PTUR+PTN=1:36±0:12 sec; DR+iR=0:57±0:13 sec; REC=2:10±0:44 sec; WO=2:03±0:31 sec), but had similar values in terms of change in apical root canal diameter (P>0.05). Conclusions: Based on this in vitro study, the type of endodontic instrument did not affect the diameter of the root canal apical third. However, PTUR with ProTaper Next had the lowest residual filling material volume and second lowest retreatment time, in flat-oval root canals in mandibular incisors.